LEGAL PHILOSOPHY PARADIGM WITH CHARACTER BASED ON HUMANS AS PEOPLE OF ANTHROPOCENTRISM - Ansari Sibarani, Fauzi (NOMOI Law Review, 2024)
Legal philosophy is a science that discusses fundamental issues about law, or the science of the nature of law. This research method uses prescriptive legal research which focuses on literature reviews to collect information from various literature regarding the legal topic being studied. The results of this research show that anthropocentrism is a very instrumentalist paradigm of environmental ethics, because the relationship between humans and nature can only be seen instrumentally. Nature is considered only as a tool for human interests. This paradigm is also selfish because it only prioritizes human interests. Philosophy plays a very important role in shaping human personality and making human life better. People with character usually have ideas about how they can shape and build their future and are able to think about how to develop it. Personality development takes a long time and involves many aspects of life, including experience, education, culture and social environment. The progress or even decline of a nation is influenced by the individual quality of its citizens.